Penilaian Kapasitas Struktur Atas Jembatan Maribaya A dengan Metode Bridge Load Rating - Agung Hari Wibowo; Chandra Kurniawan (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
The important function of bridges in the transportation system requires bridge performance to always be in prime condition. The reliability of the bridge structure in carrying the traffic load on it is the main parameter to guarantee the performance of a bridge. Bridge performance can always be maintained by regularly checking. This article about the evaluation of existing bridges takes a case study of the Maribaya A Bridge which was built in 1972 and is located on Jalan Bts. Tegal City – Bts. The city of Pemalang, which is part of the Pantura, is known for having a heavy load. The Maribaya A Bridge has a total of three spans, spans 1 and 3 with a length of 15 m, and span 2 with a length of 30 m. The evaluation was carried out on the superstructure, the cast in situ type girder components. The analysis is carried out using the rating factor method by comparing the capacity of the girder with the traffic load above it. The calculation results show that the rating factor value for spans 1 and 3 is 0.40 and for span 2 is 0.19. The rating factor value for the entire span shows <1.00, means that the superstructure capacity of the Maribaya A Bridge is no longer able to withstand the traffic load. Serious attention is needed, bridge reconstruction is absolutely necessary.